Morphology of Tarutung City (International Journal of Architecture and Urbanism, 2022)
Tarutung is a sub-district town that is the capital of North Tapanuli City, North Sumatra province, Indonesia. Tarutung City is a district that has the smallest area but has the highest population density. This study aims to find patterns of organizational structure Tarutung City space uses the morphological approach of Tarutung City. Method used is a qualitative method with a descriptive analysis approach. This study found that the pattern of a compact city with linear spreading follows the road, on the morphology of the city structure it is oriented towards the center of government, namely the regent's office, and the Regional People's Representative Council office, and on the visual morphology Tarutung City has a special landmark, namely the Cross of Love which is a building to commemorate the event of the spread of Christianity in the Batak lands which was pioneered by a German missionary, namely Dr. I.L. Nommennsen.